Physiological effects of parasitization by Nasonia vitripennis on its host pupae of Boettcherisca peregrina - ZHANG Tao; ZHANG Zhong; LI Kai; YE Gong-yin; HU Cui (浙江大学学报. 农业与生命科学版, 2005)
The parasitization by Nasonia vitripennis (Hymenoptera: Pteromalidae) could result in marked changes in hemocyte population and composition and level of soluble proteins as well as the soluble sugar level in the hemolymph of Boettcherisca peregrina pupae. Total hemocyte counts and the counts of plasmatocyte and granulocyte were significantly larger in parasitized pupae than in unparasitized ones, while both levels of soluble proteins and soluble sugars in the hemolymph of parasitized pupae were found to be clearly lower than that in unparasitized ones. The SDS-PAGE electrophoresis showed some differences in the electrophoresis profile of hemolymph soluble proteins between parasitized and unparasitized pupae. The richness of three protein bands with molecular weight of 28 kD, 32 kD and 100 kD in parasitized pupae was significantly lower than that in unparasitized ones since the 2nd day after parasitism. The reverse was true for another protein band with molecular weight of about 14 kD.